2018
DOI: 10.1186/s12943-018-0925-7
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of tumor suppressor BMP5 in sporadic colorectal cancer: a genomic and transcriptomic profiling based study

Abstract: BackgroundAlthough the genetic spectrum of human colorectal cancer (CRC) is mainly characterized by APC, KRAS and TP53 mutations, driver genes in tumor initiation have not been conclusively demonstrated. In this study, we aimed to identify novel markers for CRC.MethodsWe performed exome analysis of sporadic colorectal cancer (sCRC) coding regions to screen loss of function (LoF) mutation genes, and carried out systems-level approaches to confirm top rank gene in this study.ResultsWe identified loss of BMP5 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Downregulated ATP6V0D2 probably functions through increasing HIF-2α expression produced by macrophage to enhance tumor vascularization and growth [49]. Previous studies showed that an elevated expression of ATP6V0D2 was found in stomach cancer specimens, whereas the expression was reduced in the colorectal and renal cancer specimens, which confirmed our findings [50,51]. But so far, as for the specific mechanism between ATP6V0D2 and ccRCC, there has been no research reported yet.…”
Section: Discussionsupporting
confidence: 88%
“…Downregulated ATP6V0D2 probably functions through increasing HIF-2α expression produced by macrophage to enhance tumor vascularization and growth [49]. Previous studies showed that an elevated expression of ATP6V0D2 was found in stomach cancer specimens, whereas the expression was reduced in the colorectal and renal cancer specimens, which confirmed our findings [50,51]. But so far, as for the specific mechanism between ATP6V0D2 and ccRCC, there has been no research reported yet.…”
Section: Discussionsupporting
confidence: 88%
“…In the digestive system, BMP-5 plays similar roles in both colorectal cancer (CRC) and pancreatic cancer. The loss of BMP-5 expression takes place as an early event in CRC where BMP-5 may dysregulate E-cadherin and then trigger tumor initiation and development [61]. Also, miR32 may target BMP-5 to help CRC development [62].…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was isolated using the QIAamp Tissue Kit (Qiagen, Dusseldorf, CA). Three cases of fresh sCRC tissue samples were used for whole‐exome sequencing (data were shown in Chen's study), while the matched blood samples were used to validate mutations present in their own cancer tissue samples. Fifty cases of FFPE sCRC tissue samples were used for the deep sequencing of SARDH exons (primers used as shown in Table S2), while their adjacent normal tissue samples were used to validate mutations present in their own cancer tissue samples.…”
Section: Methodsmentioning
confidence: 99%